PENERAPAN MARKETING MIX PADA PERGURUAN TINGGI - Scorita, Kurnia Budhy; Handayani, Febbie (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
The number of private universities is more than public universities, of course the existence of a number of private universities is very much the cause of the emergence of great competition among private universities that are competing to form a good image of the institution in an effort to attract public attention, especially attracting interest. prospective students thus private universities can develop various efforts based on marketing concepts, especially the marketing mix with the approach of eight indicators of product, price, promotion, place, people, process, physical evidence, customer service. This study uses a qualitative research approach with research methods based on descriptive literature review of the theory of marketing mix service products with an approach to eight indicators including product management, price, promotion, place, people, process, physical evidence, customer service and based on several research results related to application of the marketing mix in universities. The results of the study show that there are eight indicators in the marketing mix that are effectively applied to universities, including the management of product, price, promotion, place, people, process, physical evidence, customer service and outside of these indicators, universities should implement efforts other than the marketing mix. which are constant, continuous, for example training, seminars and open house